Public and private transaction costs in agri-environmental schemes : a case study on a site-specific grassland extensification scheme in Hesse, Germany - Weber, Anja; Justus Liebig University Giessen (My University, 2014)
Agri-environmental schemes (AES) have become the most important policy instrument of the Common Agricultural Policy (CAP) to foster the provision of environmental goods via agriculture. Farmers receive public payments when they carry out agri-environmental commitments. Besides the costs for payments to farmers, transaction costs - as scheme organizational costs - emerge for both farmers and implementing administrations.This cumulative thesis addresses some unexplored aspects. It explains intra-scheme variances in magnitude and composition of public as well as private TCs with the help of a case study approach, taking the influence of the regulatory framework of the CAP explicitly into account. With the help of both quantitative and qualitative data and methods, the thesis investigates Reasons for differences in private TCs (Article 1, see chapter 5) Influences of the CAP/EAFRD regulations on public TCs and resulting spillovers onto private TCs (Article 2, see chapter 6), Differences in local public TCs (Article 3, see chapter 7).Overall, the results reveal that a) the EAFRD regulations set the framework for AES design and implementation and thus influences the magnitude of both public and private TCs, b) the CAP framework causes allocative and distributive effects on both public and private TCs in Hesse and thus affects TC composition and incidence, and finally c) the degree of this impact varies subject to foremost actor-related factors, which d) provides an explanation for intra-scheme TC variances. By this, the results of the thesis complement and extend existing findings and may help for the future design of agri-environmental schemes.

Agrar-Umweltmaßnahmen stellen mittlerweile das wichtigste Instrument der Gemeinsamen Agrarpolitik dar, um die Bereitstellung ökologischer Leistungen durch die Landwirtschaft zu fördern. Landwirte erhalten Zahlungen der öffentlichen Hand, wenn sie sich zur Einhaltung bestimmter umweltverträglicher agrarischer Wirtschaftsweisen verpflichten. Für die Umsetzung eines solchen Programms fallen jedoch sowohl bei Verwaltung als auch beim Landwirt Transaktionskosten an.Diese kumulative Dissertation untersucht einige bisher nichtadressierte Aspekte solcher öffentlicher und privater Transaktionskosten mit Hilfe eines exemplarischen, EU-kofinanzierten Grünlandextensivierungsprogramms unter Einsatz von qualitativen und quantitativen Daten und Analysemethoden. Im Einzelnen untersucht die Arbeit- Ursachen der Unterschiede im Aufkommen privater Transaktionskosten (Artikel 1)- Den Einfluss der GAP (ELER)-Regulierungen auf Transaktionskosten der hessischen Agrarverwaltung und resultierende Überschwappeffekte auf die Transaktionskosten der Landwirte (Artikel 2)- Gründe für unterschiedliche öffentliche Transaktionskosten in den hessischen Landkreisen.Die Ergebnisse zeigen, dass a) das ELER Rahmenwerk das Aufkommen öffentlicher und privater Transaktionskosten in Hessen maßgeblich beeinflusst, b) allokative und distributive Effekte entfaltet, die auch die Zusammensetzung der jeweiligen Transaktionskosten beeinflussen, dass c) der Grad der Beeinflussung von im Wesentlichen von akteursbezogenen Faktoren abhängt, was wiederum d) eine Erklärung für Varianzen in öffentlichen und privaten Transaktionskosten innerhalb dieses Programms bietet. Die Ergebnisse komplementieren und ergänzen die bisherige Forschung und leisten einen Beitrag zum besseren Verständnis anfallender Transaktionskosten, was für die künftige Ausgestaltung von Agrar-Umwelt-Maßnahmen wichtig ist.
Öffentliche und private Transaktionskosten in Agrar-Umweltmaßnahmen : das Fallbeispiel standortspezifische Grünlandextensivierung in Hessen, Deutschland
Keywords: Agrarökonomie (VWL); Agrarwissenschaften und Umweltmanagement; Agrar-Umweltmaßnahmen; Transaktionskosten; Hessen; Agri-environmental schemes; transaction costs; case study; Germany; ddc:630